Comparison between ethanol and hexane for oil extraction from Quercus suber L. fruits (Grasas y Aceites, 2003)
The aim of this study was to (i) evaluate the feasibility of replacing n -hexane with ethanol for the extraction of oil from Quercus suber fruits and (ii) optimize, at lab scale, sample preparation and extraction time for both solvents used ( n -hexane vs . anhydrous ethanol). For both solvents, the effect of the conditioning process on extraction yield was evaluated. Therefore, a full factorial design was used as a function of four variables: dehulling (with vs . without husks), and thermal treatment of the crushed material (40ºC vs . 75ºC), at different times (5 min vs . 120 min) and pressures (10 kPa vs. 100 kPa). Higher oil yields were obtained with n -hexane when dehulled fruits were conditioned under atmospheric pressure. Better yields were obtained with n -hexane, when dehulled material was treated at 75ºC for 90 min. Ethanol was not adequate for oil extraction from Quercus fruits, since other materials rather than oil were also extracted.